Computer anxiety and skills: A survey amongst undergraduate student from rural areas in Malaysia - Wan Husin, Wan Nor Al-Ashekin; Thinakaran, Rajermani; Wan Husin, Wan Zakiyatussariroh (2016)
With the rapid growth of technology, nowadays people are using Information Communication Technology (ICT) as a tool in all aspects of life. Hence, competitiveness in ICT is increasing worldwide.Malaysia towards Vision 2020 has implemented many initiatives in ICT transformation for community including students from the rural areas.This research is conducted to investigate level of computer anxiety and skills amongst undergraduate students from rural areas in Malaysia.The study was done through distribution of 250 questionnaire samples to year one students from non-computing programs who are enrolled computer literacy subject at one of the private higher institutions in Negeri Sembilan and 128 responded.The results of the study show that the undergraduate students are not anxious using computer in their learning environment.The students also show good level of computer skills. These results are based on the student’s perception and the results also indicate that the students have built their computer skills since in lower level of education through the government initiatives.